Learning and Education for a Better World: The Role of Social Movements. Budd L. Hall, Darlene E. Clover, Jim Crowther and Eurig Scandrett (Eds.) (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
My overall impression, after reading the twelve chapters of this book, is of resistance –  like shafts of light in all corners of the globe breaking through the gloom of a world fixated on greed. As an activist, I was excited to read about creative social movements and take lessons for my own involvement; as an adult educator, there was much to ponder about how and whether a revolutionary message can be imparted from the comfort of state-funded institutions.